In operando measurements of liquid water saturation distributions and effective diffusivities of polymer electrolyte membrane fuel cell gas diffusion layers. (20th August 2016) - Chevalier, S.; Lee, J.; Ge, N.; Yip, R.; Antonacci, P.; Tabuchi, Y.; Kotaka, T.; Bazylak, A.
Abstract: In this work, the in operando determinations of liquid water saturation and corresponding effective diffusivities were measured for polymer electrolyte membrane fuel cell gas diffusion layers (GDLs). Through-plane liquid water saturation profiles were obtained by combining liquid water thicknesses measured from in operando synchrotron X-ray radiography and the GDL porosity distributions from ex situ X-ray computed tomography. The effective diffusivity of these partially saturated GDLs were determined from electrochemical impedance spectroscopy (EIS) measurements combined with results from our one-dimensional fuel cell impedance model. The ratio of the effective diffusivity of the GDL to the oxygen bulk diffusivity was found to follow a power law relationship, ( 1 − s a v g ) 2.80 which is in agreement with measurements typically reported in the literature from limiting current and three-dimensional mass transport models. The methodology presented in this paper provides a novel, in operando and complementary alternative technique for measuring the effective diffusivity of partially saturated GDLs.